2018
DOI: 10.1039/c7ra13119d
|View full text |Cite
|
Sign up to set email alerts
|

Nano metal oxides as efficient catalysts for selective synthesis of 1-methoxy-2-propanol from methanol and propylene oxide

Abstract: Nano metal oxides such as Fe2O3, Fe3O4, CuO, NiO, ZnO and SnO2 were prepared and characterized using XRD, SEM and TEM analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Different catalytic systems relevant to this process are reported in the literature. These systems include alkaline catalysts (hydroxides of alkali and alkaline‐earth metals),, amino‐functionalized SiO 2 , immobilized ionic liquid 1,1,3,3‐tetramethylguanidinium lactate on bentonite and SBA‐15 (IL/Support),, M x O y (M – Cu, Fe, Zn, Sn, and Ni), MgO,, metal phosphate molecular sieves, Al‐, Ga‐, Zr‐, and Zr, Al‐pillared clays (PILCs), natural and synthetic layered double hydroxides (LDHs) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different catalytic systems relevant to this process are reported in the literature. These systems include alkaline catalysts (hydroxides of alkali and alkaline‐earth metals),, amino‐functionalized SiO 2 , immobilized ionic liquid 1,1,3,3‐tetramethylguanidinium lactate on bentonite and SBA‐15 (IL/Support),, M x O y (M – Cu, Fe, Zn, Sn, and Ni), MgO,, metal phosphate molecular sieves, Al‐, Ga‐, Zr‐, and Zr, Al‐pillared clays (PILCs), natural and synthetic layered double hydroxides (LDHs) …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this material contains both Lewis acid sites attributed to Zn 2+ ions (LAS) and basic sites associated with the imidazole units in its framework . Because of these properties, ZIF‐8 was successfully used as the catalyst for the conversion of CO 2 to cyclic carbonates,, Knoevenagel reactions, aldol condensation and trans‐esterification of vegetable oil with alcohols . Therefore, this material is a good candidate for the synthesis of PGME from PO and methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, nanozinc oxide, nanotitanium dioxide, nanomagnesium oxide, and other nanosized metal oxides of the main element of the second cycle and the third cycle of the subgroup elements have a wider application range and greater influence. [19][20][21][22] Rao et al 23 found that the mechanical properties of polyvinyl alcohol composite film with copper oxide nanoparticles as filler were enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Due to that nanometal oxides have small particle size, high surface energy, attractive particles, great tendency of automatic aggregation, and are prone to agglomeration, they have a good affinity with rubber molecules, therefore, they are very popular in the research of composite materials. Among them, nanozinc oxide, nanotitanium dioxide, nanomagnesium oxide, and other nanosized metal oxides of the main element of the second cycle and the third cycle of the subgroup elements have a wider application range and greater influence 19–22 . Rao et al 23 found that the mechanical properties of polyvinyl alcohol composite film with copper oxide nanoparticles as filler were enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, various catalysts have been developed for the coupling reaction of CO 2 with epoxides, such as metal oxides, 20,21 alkali metal salts, 22,23 organic bases, 24,25 ionic liquids, [26][27][28] metal complexes, [29][30][31] and so on. Prominent among these are the homogeneous catalyst systems based on well-dened metal complexes.…”
Section: Introductionmentioning
confidence: 99%